Mindful Change in Times of Permanent Reorganization Organizational, Institutional and Sustainability Perspectives - Becke, Guido; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Since the 1990ies, organizations from different sectors have been operating in increasingly dynamic socio-economic environments characterized by unexpected events and instability. Organizations tend to adjust to dynamic environments by change initiatives promoting permanent reorganization. Such change initiatives often induce unintended effects, e.g. an erosion of trust, the violation of ‘psychological contracts’ in employees’ eyes or a decrease in organizational effectiveness. This book explores and analyzes whether such unintended effects can be anticipated or constructively dealt with by mindful change. The latter refers to the concept of organizational mindfulness that originally is linked to risk and safety research, e.g. in respect to ‘High Reliability Organizations’. In this book, organizational mindfulness is re-conceptualized addressing organizational change in the perspective of organizational sustainability. Moreover, it is explored how institutions foster or restrict organizations’ capability of organizational mindfulness in change processes. .
Introduction -- Organizational Mindfulness - A concept for mindful organizational change ? -- Dialogue - A concept for designing organizational change mindfully -- Trust as a challenge to organizational change -- Mindfulness in social change - A societal perspective -- Perspectives.
Keywords: Personnel management; Organization; Planning; Economic sociology; Labor economics; Human Resource Management; Organization; Organizational Studies, Economic Sociology; Labor Economics